Highlander [videorecording (DVD)] - Lambert, Christopher, 1957-; Mulcahy, Russell, 1953-; Hart, Roxanne, 1952-; Brown, Clancy; Connery, Sean (Studio Canal, 2016)
After Scottish clansman Connor Macleod discovers his true identity as a member of a legion of immortals, he embarks on a legendary journey spanning continents and centuries, eventually landing in modern-day New York City. Connor faces his ultimate test when other immortals begin to appear in the city, leading to a titanic showdown where only one can claim victory.